The Effect of Group Guidance with The Bibliotherapy Method on Increasing ABH Resilience in LPKA Class II A Bengkulu (Martabat: Jurnal Perempuan dan Anak, 2022)
This study aims to 1) determine the influence of group guidance with the Biblioterpahy method on increasing ABH resilience in LPKA Kelas II A Bengkulu. The type of research used is action research or Action Research. The subject of the study was Children Facing the Law (ABH) who underwent the coaching process at LPKA Class II A Bengkulu which was selected using pruposive sampling techniques, so that 10 ABH people who met the creteria were obtained. The research instrument uses questionnaires, observation sheets and interviews. Data analysis techniques consist of 4 stages, namely. data selection, data correction, data interpretation and inference. The findings of the study revealed that; group guidance with the biblioteraphy method can help develop and improve ABH resilience, although in the aspect of self-confidence or (self efficacy) it still needs further strengthening and coaching, thus it can be concluded that group guidance with the biblioteraphy method has an effect in increasing ABH releintion in LPKA Kelas II A Bengkulu Class II A Bengkulu. Keywords: : group guidance; biblioterphy; Resilience, Children Face the Law